The Room of Many Colours : A Treasury of Stories for Children - Ruskin Bond (India Penguin Random House India, 2014)
For over five decades, Ruskin Bond has written charming tales that have mesmerised readers of all ages. This collection brings together his finest stories for children in one volume. Published previously as A Treasury of Stories for Children, this attractive rejacketed edition includes two new stories, 'The Big Race' and 'Remember This Day'. Filled with a rich cast of characters and superb illustrations, The Room of Many Colours: A Treasury of Stories for Children is the definitive book for all Ruskin Bond fans and truly a collector's Item.